Sapphique [compact disc, unabridged] - Fisher, Catherine, 1957- (Random House/Listening Library, 2010)
After his escape from the sentient prison, Incarceron, Finn finds that the Realm is not at all what he expected, and he does not know whether he is to be its king, how to free his imprisoned friends, or how to stop Incarceron's quest to be free of its own nature.